Experimental study of brackets adhesion with a novel enamel-protective material compared with conventional etching - Alberto-Carlos Cruz-González; Edgar Delgado-Mejía (Saudi Dental Journal)
Introduction: A reliable adhesion between fixed devices and dental surfaces is a key factor for the clinical success of any orthodontic treatment. Adhesion preparation is associated with damages related to abrasive cleaning, enamel structure defacing caused by etching, enamel loss when removing resin remnants at orthodontic treatment finishing stage or when conditioning surface for adhesive failure and fractures at bracket removal. Aim: The objective of this study was to compare the shear bond strength of metallic brackets to enamel adhered with a novel non-damaging and remineralizing material for enamel versus the traditional 37% phosphoric acid etching. Material and methods: 75 Premolars collected from 15- to 40-years old healthy donors requiring extraction were collected. The teeth were then randomly divided into three groups (n = 25). One group was used for the experimental new method (EX), the second for the conventional phosphoric acid etching (PA) method and the third group was left without any treatment (NT). The metallic brackets were fixed with Transbond® XT adhesive and composite resin polymerized for 40 s with a halogen photocuring lamp. The shear bond strength was quantified by means of a universal testing machine at 1 mm/min crosshead speed and a load cell of 1 kN. Statistical analysis used: Tests of normality, adjustment of the data to a root square, a one-way ANOVA and Tukey tests were performed. Results: Statistically significant differences between the NT (1.4 MPa), PA (32.1 MPa) and EX (9.7 MPa) groups were observed. Conclusions: The experimental material for conditioning human enamel induces calcium phosphates crystals on the enamel surface and improves the bond strength in comparison to the NT group. Keywords: Dental enamel, Orthodontic brackets, Dental debonding, Orthodontic adhesives (MeSH)